The emerging roles of irisin in vascular calcification - Wang, Shuangshuang; Hu, Siwang; Pan, Yuping (Frontiers in Endocrinology, 2024)
Vascular calcification is a common accompanying pathological change in many chronic diseases, which is caused by calcium deposition in the blood vessel wall and leads to abnormal blood vessel function. With the progress of medical technology, the diagnosis rate of vascular calcification has explosively increased. However, due to its mechanism’s complexity, no effective drug can relieve or even reverse vascular calcification. Irisin is a myogenic cytokine regulating adipose tissue browning, energy metabolism, glucose metabolism, and other physiological processes. Previous studies have shown that irisin could serve as a predictor for vascular calcification, and protect against hypertension, diabetes, chronic kidney disease, and other risk factors for vascular calcification. In terms of mechanism, it improves vascular endothelial dysfunction and phenotypic transformation of vascular smooth muscle cells. All the above evidence suggests that irisin plays a predictive and protective role in vascular calcification. In this review, we summarize the association of irisin to the related risk factors for vascular calcification and mainly explore the role of irisin in vascular calcification.